A survey of analysis software for array-comparative genomic hybridisation studies to detect copy number variation - Karimpour-Fard Anis; Dumas Laura; Phang Tzulip; Sikela James M; Hunter Lawrence E (Human Genomics, 2010)
Abstract Copy number variants (CNVs) create a major source of variation among individuals and populations. Array-based comparative genomic hybridisation (aCGH) is a powerful method used to detect and compare the copy numbers of DNA sequences at high resolution along the genome. In recent years, several informatics tools for accurate and efficient CNV detection and assessment have been developed. In this paper, most of the well known algorithms, analysis software and the limitations of that software will be briefly reviewed.